2001
DOI: 10.1046/j.1365-313x.2001.01006.x
|View full text |Cite
|
Sign up to set email alerts
|

Members of the tomato LeEIL (EIN3‐like) gene family are functionally redundant and regulate ethylene responses throughout plant development

Abstract: SummaryThe plant hormone ethylene regulates many aspects of growth, development and responses to the environment. The Arabidopsis ETHYLENE INSENSITIVE3 (EIN3) protein is a nuclear-localized component of the ethylene signal-transduction pathway with DNA-binding activity. Loss-of-function mutations in this protein result in ethylene insensitivity in Arabidopsis. To gain a better understanding of the ethylene signal-transduction pathway in tomato, we have identi®ed three homologs of the Arabidopsis EIN3 gene (LeE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
164
0
2

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(175 citation statements)
references
References 44 publications
9
164
0
2
Order By: Relevance
“…Because EIN3 and its close homolog EIL1 functionally overlap (Chao et al, 1997;Tieman et al, 2001;Binder et al, 2007;An et al, 2010), we studied ein3 eil1 double mutants instead of ein3 single mutants, to preclude the functional redundancy and the possibly compromised phenotype of the single mutants (see below). Compared with the wild type, ein3 eil1 plants exhibited a delayed-senescence phenotype ( Figure 2A).…”
Section: Ein3 Transcript Levels and Ein3 Activity Increase During Leamentioning
confidence: 99%
“…Because EIN3 and its close homolog EIL1 functionally overlap (Chao et al, 1997;Tieman et al, 2001;Binder et al, 2007;An et al, 2010), we studied ein3 eil1 double mutants instead of ein3 single mutants, to preclude the functional redundancy and the possibly compromised phenotype of the single mutants (see below). Compared with the wild type, ein3 eil1 plants exhibited a delayed-senescence phenotype ( Figure 2A).…”
Section: Ein3 Transcript Levels and Ein3 Activity Increase During Leamentioning
confidence: 99%
“…However, tomato contains four EIL proteins, which appear to act redundantly in ethylene signal transduction, and only downregulation of multiple genes results in a nonripening phenotype (Tieman et al, 2001). The expression of the other three known tomato EIL genes was detected, but not significantly altered, suggesting that the ethylene response is normal in FUL1/2 Differences between FUL1/2 RNAi fruits and the fruits of their wild-type siblings are represented as negative or positive fold ratios of the mean gas chromatography-mass spectrometry responses.…”
Section: Ful1/2 Act Downstream or Independent Of The Ethylene Pathwaymentioning
confidence: 99%
“…Tomato In tomato, four EIN3-like (EIL) genes (LeEIL1-LeEIL4) have been isolated (Tieman et al 2001;Yokotani et al 2003). Reduced expression of tomato LeEIL genes by antisense technology modulates ethylene responses, including leaf epinasty, flower senescence and fruit ripening (Tieman et al 2001).…”
Section: Recent Understanding On Ripening Behaviour Of Fruitsmentioning
confidence: 99%
“…Reduced expression of tomato LeEIL genes by antisense technology modulates ethylene responses, including leaf epinasty, flower senescence and fruit ripening (Tieman et al 2001). Ito et al (2008) demonstrated that the ripening inhibitor (RIN protein) exhibits transactivator activity because it binds to the promoter region of LeACS2.…”
Section: Recent Understanding On Ripening Behaviour Of Fruitsmentioning
confidence: 99%